2008
DOI: 10.1007/s10482-008-9292-5
|View full text |Cite
|
Sign up to set email alerts
|

Th1-type immune response to infection by pYV-cured phoP-phoQ null mutant of Yersinia pseudotuberculosis is defective in mouse model

Abstract: The PhoP-PhoQ two-component system of Yersinia pseudotuberculosis, a Gram-negative enteric pathogen which causes a variety of gastrointestinal and extraintestinal infections in humans, has been shown to be necessary for virulence. A phoP-phoQ null mutant of a strain of Y. pseudotuberculosis cured of its native plasmid pYV was obtained and studied for generation of immune response in mouse model following intravenous inoculation. The phoP-phoQ null mutant elicited much weaker IgG antibody response to whole cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…In 2009, Kumar et al ., showed that a virulence-plasmid cured Y. pseudotuberculosis Δ phoPQ mutant is diminished in the T h 1-type immune response in a murine systemic infection model following intravenous inoculation [45]. However, a deeper dissection of the PhoP-driven immune response in mice infected by the natural intragastric route is so far missing.…”
Section: Resultsmentioning
confidence: 99%
“…In 2009, Kumar et al ., showed that a virulence-plasmid cured Y. pseudotuberculosis Δ phoPQ mutant is diminished in the T h 1-type immune response in a murine systemic infection model following intravenous inoculation [45]. However, a deeper dissection of the PhoP-driven immune response in mice infected by the natural intragastric route is so far missing.…”
Section: Resultsmentioning
confidence: 99%
“…Postinfectious sequelae include reactive arthritis and erythema nodosum. Yersinia pseudotuberculosis also causes a variety of gastrointestinal and extraintestinal infections in humans (Kumar et al , 2009). Encoded by the caf gene cluster (Fig.…”
Section: Applications Of Adhesive Organelles Assembled With the Chapementioning
confidence: 99%
“…For the lymphoproliferation assay, five mice from each group (except the vaccine group) were sacrificed, and their spleens were removed aseptically. Spleen cell proliferation was determined by a method described previously (25). Experiments were carried out in triplicate wells for each mouse, and the results are expressed as the mean specific absorbance by subtracting the absorbance at 600 nm from that at 570 nm, after subtracting the reading for cells without antigen at each wavelength.…”
Section: Vol 78 2010 Comparative Proteomic Analysis Of C Perfringementioning
confidence: 99%